A not so meet cute - Quinn, Meghan (Quinn, Meghan. Cane brothers, 2023)
"How did you two meet?" It's the quintessential question asked to every couple, and the answer is usually some bubbly, lovey-dovey tale of being struck in the bum by Cupid's arrow. But Lottie Gardner's meet-cute was a little different. She was trolling a wealthy neighborhood in Beverly Hills, searching for someone to take her as his bride--you know, to make the arch nemesis who just fired her jealous. And billionaire Huxley Cane was conveniently stomping around the block like some sort of gorgeous ogre, mumbling about a business deal gone wrong. That's when they bump into each other. No sparks. No fireworks. Not even the first seed of blossoming love. But the next thing Lottie knows, she's scarfing down chips and guac, listening to Huxley lay out his problems, and then he tells her: He lied to a crucial client, and he needs a huge favor. A fake fiancée. He's talking living in his mansion together, going on intimate double-dates, and pretending they're head-over-heels in love...and engaged. It's ridiculous, but people do ridiculous things when they're desperate. And Lottie and Huxley both reek of desperation. So, she strikes up the deal. Except her one mistake might be accidentally falling for the incomparable, insufferable Huxley Cane"--